Implementasi E-Relationship Marketing melalui Media Sosial dalam Menjaga Loyalitas Jemaah di Era Digital pada PT. Al-Amar Madani Masyhur Medan: Laporan Hasil Magang - Nur Madiah Harahap; Indah Salsabila Harahap; Salman Salman; Mhd. Habib Alhabsyi; Muhammad Irhamsyah; Hafis Hanafi Nasution (Jurnal Riset Rumpun Agama dan Filsafat, 2024)
This study aims to analyze the E-Relationship Marketing strategy implemented by PT. Travel Al-Amar Madani Masyhur Medan through social media in an effort to maintain pilgrim loyalty amidst the increasingly competitive Umrah travel industry in the digital era. The research method used is descriptive qualitative with a case study approach. Data collection was conducted through in-depth interviews with management and pilgrims, observation of social media activities (Instagram, Facebook, and WhatsApp), and documentation. Data analysis used data reduction, data display, and conclusion drawing techniques. The results show that the implementation of E-Relationship Marketing is carried out through four main dimensions: service personalization, digital community building, responsive interaction, and consistency of Islamic brand character. The use of social media is proven effective in increasing trust and emotional closeness of pilgrims, leading to loyalty in the form of repeat orders and recommendations (advocacy). The main obstacle found is the digital literacy gap among elderly pilgrims, which the company addressed through simpler and more intensive communication approaches on the WhatsApp platform.